EMPOWERING ISLAMIC COMMUNITY IN UNDERSTANDING DEMOCRACY AND SHURA THROUGH THE WASATHIYAH DA‘WA MOVEMENT IN INDONESIA (JOURNAL OF INDONESIAN ISLAM, 2024)
The comprehension of democracy and Shura by the Islamic community plays a crucial role in enhancing participation in democratization processes. However, a lack of thorough understanding may lead to disparities and disagreements. The Wasathiyah Islamic Preaching Movement offers a solution by facilitating a deep understanding of both concepts. This article employs a literature review methodology, analyzing seven articles across three databases—PubMed, Scopus, and SpringerLink—to explore the empowerment efforts within the Islamic community regarding democracy and the principles of Shura, as facilitated by the Wasathiyah Islamic Preaching Movement in Indonesia. The findings suggest that the empowerment of the Islamic community in understanding democracy and Shura, through the Wasathiyah Islamic Preaching Movement in Indonesia, is achieved through moderation (tawasuth), balance (tawazun), tolerance (tasamuh), and justice (ta’addul). This article aims to serve as a resource for society to mitigate the potential for disparities and disagreements in applying democratic principles and Shura.